Addiction, Modernity, and the City - Smith, Christopher B.R. (Taylor & Francis, 2023)
Examining the interdependent nature of substance, space, and subjectivity, this book constitutes an interdisciplinary analysis of the intoxication indigenous to what has been termed "our narcotic modernity." The first section – Drug/Culture – demonstrates how the body of the addict and the social body of the city are both inscribed by "controlled" substance. Positing addiction as a "pathology (out) of place" that is specific to the (late-)capitalist urban landscape, the second section – Dope/Sick – conducts a critique of the prevailing pathology paradigm of addiction, proposing in its place a theoretical reconceptualization of drug dependence in the terms of "p/re/in-scription." Remapping the successive stages or phases of our narcotic modernity, the third section –Narco/State – delineates three primary eras of narcotic modernity, including the contemporary city of "safe"/"supervised" consumption. Employing an experimental, "intra-textual" format, the fourth section –Brain/Disease – mimics the sense, state or scape of intoxication accompanying each permutation of narcotic modernity in the interchangeable terms of drug, dream and/or disease. Tracing the parallel evolution of "addiction," the (late-)capitalist cityscape, and the pathological project of modernity, the four parts of this book thus together constitute a users’ guide to urban space.